Human Resource Strategy: Formulation, Implementation, and ImpactHuman Resource Strategy: Formulation. Implementation, and Impact, by BambergerPeter and MeshoulamIlan. Thousand Oaks, CA: Sage, 2000. - Mahoney, Joseph T.; Wright, Patrick M. (Academy of Management Review, 2000)
Peter Bamberger and Ilan Meshoulam's new book, “Formulation, Implementation, and Impact,” presents the best attempt available to provide an overarching framework for integrating the large and varied body of research relating to the links between strategy and human resource management (HRM). Their goal, it seems, is not only to review this substantial literature but also to provide a model of HR strategy that enables researchers to see both the consistencies and inconsistencies that exist within this literature. While not perfect, this attempt goes far beyond any other in both the breadth of literature covered and in the authors' ability to integrate what on the surface appears to be a mishmash of empirical and theoretical efforts related only by their use of the term strategic HRM.